Measures of outcome in lung cancer screening: maximising the benefits - Young, Robert Peter; Hopkins, Raewyn Janice (Journal of Thoracic Disease, 2016)
In their article, Miller and colleagues report on the survival results of smokers enrolled in their communitybased multicentre computed tomography (CT) screening program for lung cancer (1). In a cohort of 1,267 primarily moderate to high risk smokers, followed with annual CT screening for 5 years, 36 subjects underwent biopsy, 30 were confirmed to have lung cancer of which 28 were primary lung cancers. Overall 5-year survival was 64% and 5-year lung cancer specific survival was 71% in the screened patients, where the overall-survival compared favourably to the 5-year survival in a group of non-screened lung cancer patients (64% vs. 19% respectively, P